2015
DOI: 10.1002/ece3.1644
|View full text |Cite
|
Sign up to set email alerts
|

Quantity over quality: light intensity, but not red/far‐red ratio, affects extrafloral nectar production in Senna mexicana var. chapmanii

Abstract: Extrafloral nectar (EFN) mediates food‐for‐protection mutualisms between plants and insects and provides plants with a form of indirect defense against herbivory. Understanding sources of variation in EFN production is important because such variations affect the number and identity of insect visitors and the effectiveness of plant defense. Light represents a potentially crucial tool for regulating resource allocation to defense, as it not only contributes energy but may help plants to anticipate future condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…, Yamawo & Hada , Izaguirre et al . ), including S. chapmanii (Jones & Koptur 2015b). Yamawo and Hada (), for example, found that EFN production in Mallotus japonicus was increased at high light intensities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…, Yamawo & Hada , Izaguirre et al . ), including S. chapmanii (Jones & Koptur 2015b). Yamawo and Hada (), for example, found that EFN production in Mallotus japonicus was increased at high light intensities.…”
Section: Discussionmentioning
confidence: 99%
“…For each plant, combined nectar volume from the five most recently matured leaves on the chosen branch was measured using 1‐, 2‐, and 10‐ μ l micropipettes. Nectar concentration was measured using a handheld refractometer, and total sugar production was estimated from the combination of these measurements (see Jones & Koptur ,b). In the results, EFN is expressed as total sugar production.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations